Improving Oral Health in Special Needs Populations: Challenges and Solutions - Muhammad Junaid Hashmi, Hussain Mujtaba Malik, Hafiz Muhammad Tufail, Saleem Adil, Asma Rafi Chaudhry, Muhammad Sami Iqbal, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Individuals with intellectual, developmental, or physical disabilities often encounterdisproportionate barriers to oral healthcare, including reduced access to preventive services,diminished capacity for daily hygiene, and behavioral or communication limitations. In this mixed